2017
DOI: 10.21608/edj.2017.76059
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nonsurgical Periodontal Therapy on Systemic Pro-inflammatory and Vascular Endothelial Biomarkers and Serum Lipid Profile in Chronic Periodontitis Patients

Abstract: The present study aimed to estimate the serum levels of vascular cell adhesion molecule-1(VCAM-1), interleukin-6 (IL-6), and lipid profile [including total cholesterol, triglycerides (TGs), high-density lipoprotein cholesterol (HDL) and low-density lipoprotein cholesterol (LDL)] in chronic periodontitis patients and to detect the association between the aforementioned cardiovascular disease risk markers and the periodontal disease severity and extent. In addition, the study also aimed to detect whether the non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…Samah H. Elmeadawy et al have shown that NSPT significantly reduces serum VCAM1 levels. The VCAM1 protein mediates the adhesion of lymphocytes, monocytes, eosinophils, and basophils to the vascular endothelium and may be involved in the development of atherosclerosis and rheumatoid arthritis (14). Another study by Cui D et al has shown reduced VCAM1 expression and macrophage/ monocyte infiltration in the vascular wall of mice treated with NSPT (15).…”
Section: Discussionmentioning
confidence: 99%
“…Samah H. Elmeadawy et al have shown that NSPT significantly reduces serum VCAM1 levels. The VCAM1 protein mediates the adhesion of lymphocytes, monocytes, eosinophils, and basophils to the vascular endothelium and may be involved in the development of atherosclerosis and rheumatoid arthritis (14). Another study by Cui D et al has shown reduced VCAM1 expression and macrophage/ monocyte infiltration in the vascular wall of mice treated with NSPT (15).…”
Section: Discussionmentioning
confidence: 99%